2008
DOI: 10.1124/dmd.108.023465
|View full text |Cite
|
Sign up to set email alerts
|

Use of Sandwich-Cultured Human Hepatocytes to Predict Biliary Clearance of Angiotensin II Receptor Blockers and HMG-CoA Reductase Inhibitors

Abstract: 35, 23, 31, 25, and 16%, respectively, and 0.943, 1.20, 0.484, 3.39, and 5.48 ml/min/kg, respectively. Cl biliary values predicted from sandwich-cultured human hepatocytes correlated with estimated in vivo hepatic clearance values based on published data (no in vivo data in humans was available for pitavastatin), and the rank order was also consistent. In conclusion, in vitro Cl biliary determined in sandwich-cultured human hepatocytes can be used to predict in vivo Cl biliary of compounds in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
56
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(75 citation statements)
references
References 23 publications
(35 reference statements)
7
56
1
Order By: Relevance
“…The accumulation of taurocholate was significantly higher in hepatocytes incubated with standard HBSS than in those incubated with Ca 2ϩ /Mg 2ϩ -free HBSS, and its BEI values ranged from 45 to 70% in SCRH and from 50 to 60% in SCHH in our experiments. These values were comparable to those in previous reports (Liu et al, 1999a;Abe et al, 2009). In contrast, no difference in the accumulation of salicylate in SCRH and SCHH was observed when they were incubated with standard HBSS or Ca 2ϩ /Mg 2ϩ -free HBSS, as demonstrated previously (Liu et al, 1999a).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The accumulation of taurocholate was significantly higher in hepatocytes incubated with standard HBSS than in those incubated with Ca 2ϩ /Mg 2ϩ -free HBSS, and its BEI values ranged from 45 to 70% in SCRH and from 50 to 60% in SCHH in our experiments. These values were comparable to those in previous reports (Liu et al, 1999a;Abe et al, 2009). In contrast, no difference in the accumulation of salicylate in SCRH and SCHH was observed when they were incubated with standard HBSS or Ca 2ϩ /Mg 2ϩ -free HBSS, as demonstrated previously (Liu et al, 1999a).…”
Section: Discussionsupporting
confidence: 82%
“…For example, Fukuda et al (2008) showed that the absolute CL bile, vitro values for some angiotensin II receptor blockers, HMG-CoA reductase inhibitors (statins), and antibiotics were approximately 20-to 200-fold lower than the CL bile, vivo values, although good correlations between CL bile, vitro and CL bile, vivo were observed (Fukuda et al, 2008). Abe et al (2008Abe et al ( , 2009) compared the CL bile, vitro of some angiotensin II receptor blockers and statins with their CL bile, vivo in both sandwich-cultured rat hepatocytes (SCRH) and sandwich-cultured human hepatocytes (SCHH), and these CL bile, vitro values were also 20-to 200-fold lower in the SCRH and approximately 20-fold lower in the SCHH than the CL bile, vivo values (Abe et al, 2008(Abe et al, , 2009). Li et al (2010) tried to improve the in vitro-in vivo correlation of the biliary clearance of drugs using SCRH by introducing an appropriate scaling factor, because CL bile, vitro was approximately 6-fold lower than CL bile, vivo based on a conventional calculation method (Li et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, the prediction of biliary excretion in humans using in vitro tools has not been established. It was reported that in vivo biliary clearance can be predicted from sandwich-cultured hepatocytes in rats and humans (Liu et al, 1999a;Abe et al, 2008Abe et al, , 2009Fukuda et al, 2008;Li et al, 2010). Although apparent biliary clearance using sandwich-cultured rat or human hepatocytes correlates to in vivo values, the differences in biliary clearance between in vitro and in vivo are more than 10-fold.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast with conventional conditions, sandwich-cultured hepatocytes maintain liver-specific functions for several days and exhibit the formation of bile canaliculi and the localization of efflux transporters on the canalicular membrane (LeCluyse et al, 1994;Talamini et al, 1997). Moreover, the biliary clearance of some drugs, such as angiotensin II receptor blockers, HMG-CoA reductase inhibitors, and ␤-lactam antibiotics, showed correlation between sandwich-cultured rat or human hepatocytes and in vivo (Liu et al, 1999a;Abe et al, 2008Abe et al, , 2009Fukuda et al, 2008;Li et al, 2010). Although previous reports have suggested that sandwich-cultured hepatocytes can be used to predict the in vivo biliary clearance of drug candidates, differences in biliary clearance based on the medium or plasma concentration are greater than 10-fold between sandwich-cultured rat or human hepatocytes and in vivo values.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro predictions can be carried out in sandwichcultured rat or human hepatocytes, which preserve cell polarity and bile canaliculi (15,16), but uptake transporter expression is not well preserved in sandwich-cultured rat hepatocytes (17) and biliary clearance can be rate limited by uptake (18). Several studies have demonstrated that in vitro measures correlate with, but underpredict, in vivo biliary clearance (19)(20)(21). Bile duct cannulation in rats is often performed, but may not scale to humans, especially as rats have greater rates of bile flow (22) and canalicular efflux transport (23), as well as increased expression (24,25) of canalicular efflux transporters.…”
Section: Introductionmentioning
confidence: 99%